On the influence of state selection on mass conservation in dynamic vapour compression cycle models. Issue 3 (4th May 2017) - Laughman, Christopher R.; Qiao, Hongtao
ABSTRACT: Many dynamic models of vapour compression systems experience nonphysical variations in the total refrigerant mass contained in the system when common modelling approaches are used. Rather than using the traditional state variables of pressure and specific enthalpy, the use of density as a state variable can eliminate these variations. The reasons for these variations are explained, and a set of test models is developed to study the effect of the state variable selection on the overall system charge. Results from both a simplified cycle model and a realistic air-source heat pump model indicate that this alternative approach has significant benefits for maintaining a fixed mass of refrigerant in the cycle.